2001
DOI: 10.2978/jsas.13.260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C and P on surface hot shortness of steel due to Cu mixed from steel scrap.

Abstract: In recent years, the necessity of the promotion of steel recycling is increasing from the viewpoints of effective usage of resources and restraint of environmental problems. In case steel scrap is recycled , surface cracks occur during hot rolling process, which poses a serious problem. This phenomenon is attributed to Cu. Copper is mixed from steel scrap and Cu in steels is enriched at the steel/scale interface by selective oxidation of Fe. This copper-enriched phase liquefies over 1083•Ž and penetrates into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Uchino et al 8) showed that the oxidation rate of a 0.1%C-0.02%P steel is much higher in LNG combustion gas than in air, whereas the oxidation rate of a 0.5%C-0.02%P steel is similar in both atmospheres and the oxidation rate of 0.5%C-0.001%P steel is a little slower in LNG than in air. Therefore, effects of atmosphere depend on the chemical composition of steel.…”
Section: Effects Of Atmosphere Of Heating Furnace and Deformation Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Uchino et al 8) showed that the oxidation rate of a 0.1%C-0.02%P steel is much higher in LNG combustion gas than in air, whereas the oxidation rate of a 0.5%C-0.02%P steel is similar in both atmospheres and the oxidation rate of 0.5%C-0.001%P steel is a little slower in LNG than in air. Therefore, effects of atmosphere depend on the chemical composition of steel.…”
Section: Effects Of Atmosphere Of Heating Furnace and Deformation Ratementioning
confidence: 99%
“…3, the effect of B on the susceptibility to the surface hot shortness cannot be explained by the effect of B on the oxidation rate. In the previous study, 8) the present authors measured an increase in the specimen weight during heating in air and the LNG combustion gas and revealed that the effects of C and P on the susceptibility cannot be explained by the effects of such elements on oxidation rate. Figure 9 shows the effect of Si on the Cu-enriched phase near the steel/scale interface of 0.1%C-0.5%Mn-0.02%P-0.5%Cu steels heated at 1373 K in air.…”
Section: Effects Of Mn and S On The Susceptibility To The Surface Hotmentioning
confidence: 99%
See 1 more Smart Citation
“…Como principal efeito negativo, o cobre favorece a ocorrência de perda de ductilidade a quente, o que corre em função do cobre ficar em solução sólida, associado a baixa solubilidade na austenita. Esta combinação de fatores dá origem a zonas enriquecidas em cobre, que fundem em temperaturas de trabalho a quente, causando perda de ductilidade e eventualmente fratura intergranular (UCHINO et al, 2001). O principal mecanismo de endurecimento do cobre em ligas de aço é por solução sólida (Item 1.2).…”
Section: Cobreunclassified
“…The alloying effect on Cu bearing steels is studied to minimize the hazardous impact of Cu. Manganese, sulphur, silicon, phosphorus, and nickel effect on Cu in steel are studied from different researches [9][10][11][12][13][14]. The effect of Cu and Sn on the oxidation mechanism of steel is studied by Konda [15,16] with a low amount of Sn and Cu.…”
Section: Introductionmentioning
confidence: 99%